Numerical investigation on the hydrodynamic characteristics of a marine propeller operating in oblique inflow - Guo, Hai-peng; Zou, Zao-jian; Wang, Feng; Liu, Yi (Applied ocean research, 2019)
•The hydrodynamic characteristics of two propellers working in oblique inflow are investigated by using CFD method.•The effects of axial inflow and lateral inflow on the hydrodynamic characteristics are analyzed separately.•A systematic analysis is carried out for the propulsive loads and side force as a function of axial and lateral advance coefficients.•A simplified model is developed for the propulsive loads and side force on propeller working in oblique inflow. The hydrodynamic characteristics of a marine propeller operating in oblique inflow are investigated by using CFD method. Two propellers with different geometries are selected as the study subjects. RANS simulation is carried out for the propellers working at a wide range of advance coefficients and incidence angles. The effects of axial inflow and lateral inflow are demonstrated with the hydrodynamic force on the propeller under different working conditions. Based on the obtained flow field details, the hydrodynamic mechanism of propeller operating in oblique inflow is analyzed further. The trailing vortex wake of propeller is highly affected by the lateral inflow, resulting in the deflected development path and the circumferentially non-uniform structure, as well as the enhanced axial velocity in slipstream. Different flow patterns are observed on the propeller blade with the variation of circumferential position. Combined with the computed hydrodynamic forces and pressure distribution on propeller, the mechanism resulting in the increase of propulsive loads and the generation of propeller side force is explored. Finally, a systematic analysis is carried out for the propulsive loads and propeller side force as a function of axial and lateral advance coefficients. The major terms that play a dominant role in the modeling of propulsive loads and propeller side force are determined through the sensitivity analysis. This study provides a deeper insight into the hydrodynamic characteristics of propeller operating in oblique inflow, which is useful to the investigation of propeller performance during ship maneuvers.